2016
DOI: 10.1111/jcpt.12384
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the economic evaluations of novel therapeutic agents in multiple myeloma: what is the reporting quality?

Abstract: Summary What is known and objective Given the increasing healthcare costs and the recent introduction of novel agents in the treatment for multiple myeloma (MM), an incurable haematologic malignancy, more efficient use of existing resources is fundamental. The objective of this study was to systematically review economic evaluations of the use of novel agents in MM and assess their reporting quality. Methods A literature search was performed in PubMed/Medline, Latin American and Caribbean Health Sciences Liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 34 publications
2
24
0
Order By: Relevance
“…The assessment criteria used in the present study—CHEERS—have been applied in a number of systematic reviews reporting the quality of pharmacoeconomic publications. [ 49 51 ] Our findings confirm that there have been an increasing number of pharmacoeconomic publications from China during the period of 2003 to 2014, and the reporting quality has also been improving significantly over time. Pharmacoeconomics has received greater attention in China, which is particularly important for resource allocations and health policy decision making.…”
Section: Discussionsupporting
confidence: 73%
“…The assessment criteria used in the present study—CHEERS—have been applied in a number of systematic reviews reporting the quality of pharmacoeconomic publications. [ 49 51 ] Our findings confirm that there have been an increasing number of pharmacoeconomic publications from China during the period of 2003 to 2014, and the reporting quality has also been improving significantly over time. Pharmacoeconomics has received greater attention in China, which is particularly important for resource allocations and health policy decision making.…”
Section: Discussionsupporting
confidence: 73%
“…In a literature search and systematic review of the economic evaluations of novel therapeutic agents in MM, Aguiar et al . 2016 argued that current economic evidence for novel agents is poor; only eight studies could be included and most found that novel agents were generally cost effective at a threshold of up to $100,000 per quality-adjusted life year, but the reporting quality of the studies was low and there was large variation in methodologies [ 29 ]. This highlights the importance of the HCRU-associated cost analyses included in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is a number of economic evaluations assessing the burden of MM [33,36,37], the conclu- Legend/Legenda: BP -starting with bendamustine-prednisone/ Započinjanje terapije protokolom bendamustine-prednisone; CTD -starting with cyclophosphamide, thalidomide, dexamethasone/Započinjanje terapije protokolom cyclophosphamide, thalidomide, dexamethasone; MPT -starting with melphalan, prednisone, thalidomide/Započinjanje terapije protokolom melphalan, prednisone, thalidomide; MPV -starting with melphalan, prednisone, bortezomib/Započinjanje terapije protokolom melphalan, prednisone, bortezomib; VCD -starting with bortezomib, cyclophosphamide, dexamethasone/Započinjanje terapije protokolom bortezomib, cyclophosphamide, dexamethasone; € -Euro/Evro sions of these studies are not easily transferable to the Serbian healthcare system, due to variations in drug availability and costs and diverse patterns of treatment between the different healthcare systems. Our analysis resulted in a higher cost of bortezomib-based protocols in comparison to thalidomide-and bendamustine-based protocols for the first-line MM treatment.…”
Section: Discussionmentioning
confidence: 99%